Rehabilitation and employment of persons with disabilities in Poland - Grzegorczyk, Joanna; Wilmowska-Pietruszyńska, Anna (European Journal of Clinical and Experimental Medicine, 2015)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. According to the current concept of disability the degree of impairment is a product of physical and psychological health as well as environmental conditions in which a disabled person lives. Therefore, it is also the society that is responsible for modifying the environment so as to improve the conditions of participation and activity of the disabled persons in social and professional life. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Objective. The objective of this work is to present the problem of rehabilitation of persons with disabilities and issues related to their employment. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Materials and method: The work is based on data published by ZUS (the Polish Social Insurance Institution), KRUS (the Agricultural Social Insurance Fund), PFRON (the State Fund for Rehabilitation of Disables Persons), Office of the Government Plenipotentiary for Disabled People and on the results of the 2011 Polish Census of Population and Housing. Also acts of Polish and international law from the last dozen of years have been analysed. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. In 2013 in Poland, 1 075 000 people received the inability to work benefit and 216 373 persons received the benefit related to inability to work on a farm. According to the Polish Research on Economic Activity of the Population (BAEL), 27.3% of disabled persons in the working age led an active professional life in 2013. It is crucial to ensure that the disabled persons access or maintain employment and thus to provide for their largest possible social inclusion. The expenses on this are an investment that pays back and even generates social and economic profits. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. It is necessary to adopt a holistic approach and to coordinate the entire process of treatment, rehabilitation and employment of persons with disabilities, taking into account employer’s co-responsibility, combination of medical, social and vocational services, appropriate counselling and application of a biopsychosocial model (ICF) in evaluating the effects of rehabilitation of the disabled persons.